Worship Education In The Al Qur’an - Repi, Predi Ari; Aidah Ritonga, Dr. Asnil; Al Farabi, Dr. Mohammad (Universitas Dharmawangsa, 2024)
The Quran is the last of the Scriptures that Allah has sent down to the Prophet Muhammad (peace be upon him) and the Prophets (Agus Salim Syukran, 2019).There are two verses in this Qur'an: The first is that God created men with understanding, enabling them to study the verses of the Quran. The second is that the Quran provides solutions for the development of the world in its various aspects.Education is an important aspect of life and continues to evolve. Then it is important to search and learn the verses of the Quran that provide guidance on the theory of education. Through this effort, the theoretical foundation of Islamic education can be strengthened. This article reviews the education of worship in the Qur'an, discusses the basis, purpose, and benefits of this education. The Qur'an reveals the basics of worship, and the benefits it brings. From here, we get complete information about the essence of worship, which can be applied practically in the context of the world of education.The above illustration makes it clear that education is an educational activity carried out with a mature, serious, and planned project. Education has rules that measure the process and purpose of education itself.